Respuesta inflamatoria en niños con desnutrición aguda grave y anemia (2008)
ABSTRACT: The treatment of the infection is still challenging in children with severe malnutrition and immunosupression. Objective: evaluate and compare inflammatory markers such as C-reactive protein (CRP) and proinflammatory cytokines in children with severe malnutrition and anemia. Methodology: levels of hemoglobin, transferrin, CRP and inflammatory markers such as cytokines IL-8, IL-1β, IL-6, IL-10, TNF-α and IL-12p70 were assessed in a group of 40 children, nutritional status was also evaluated.10 were classified with marasmus, 10 with kwashiorkor, 10 well nourish with anemia and 10 well nourish with no anemia. Results: C-reactive protein was significantly higher in undernourishment children than in well nourish children. Levels of proinflammatory cytokines were higher in children with kwashiorkor along by well nourish children with anemia, children with marasmus and well nourish children with no anemia. Hemoglobin was no correlated with levels of IL-8 (r=-0,409 p=0,009), IL-6 (r=-0,442 p=0,004) and IL-10 (r=-0,436 p=0,005). Conclusion: malnourished children could develop an inflammatory condition presenting high levels of inflammatory markers such as C-reactive protein (CRP) and proinflammatory cytokines. These results suggest that proinflammatory cytokines may participate in the pathogenesis of anemia in malnourished or well nourished patients.